ANALISIS KESALAHAN SISWA SMA DALAM MATERI PERSAMAAN DAN PERTIDAKSAMAAN NILAI MUTLAK - Lesmana, Surya (IKIP Siliwangi, 2022)
This study aims to describe the mathematics learning errors of SMA Mekarwangi class X students in absolute value equations and inequalities. This research was conducted on students of SMA Mekarwangi class X who have implemented the 2013 curriculum. The type of approach in this research is a qualitative approach. The test description method according to me is 4 questions with different error rates. The data processing technique of the final test results obtained a conclusion that students' errors were in the form of facts, as many as 20,35% of students had difficulty in finding absolute values so that they could find the concept of absolute value, as many as 30,65% of students had difficulty managing the concept of absolute value so that they obtained absolute value derivatives, 35,75% of students have difficulty in drawing graphs of absolute values so that students are skilled in drawing absolute values, 70.15% of students have difficulty solving problems related to absolute values.